Expression of the agmatine deiminase pathway in Enterococcus faecalis is activated by the AguR regulator and repressed by CcpA and PTS(Man) systems - (:unkn) unknown (Public Library of Science, 2013)
Although the agmatine deiminase system (AgDI) has been investigated in Enterococcus faecalis, little information is available with respect to its gene regulation. In this study we demonstrate that the presence of exogenous agmatine induces the expression of agu genes in this bacterium. In contrast to the homologous and extensively characterized AgDI system of S. mutants, the aguBDAC operon in E. faecalis is not induced in response to low pH. In spite of this, agmatine catabolism in this bacterium contributes by neutralizing the external medium while enhancing bacterial growth. Our results indicate that carbon catabolic repression (CCR) operates on the AgDI system via a mechanism that involves interaction of CcpA and PSer-HPr with a cre site found in an unusual position considering the aguB promoter (55 nt upstream the +1 position). In addition, we found that components of the mannose phosphotransferase (PTSMan) system also contributed to CCR in E. faecalis since a complete relief of the PTS-sugars repressive effect was observed only in a PTSMan and CcpA double defective strain. Our gene context analysis revealed that aguR is present in oral and gastrointestinal microorganisms. Thus, regulation of the aguBDAC operon in E. faecalis seems to have evolved to obtain energy and resist low pH conditions in order to persist and colonize gastrointestinal niches.
Keywords: Agmatine; Enterococcus faecalis; Gene expression regulation; Molecular sequence data; Operon